Conflict Management in Improving the Organizational Climate of a Madrasah: A Case Study at MA Mutiara Sunggal - Putri Syahri; Siti Rukhaiyah; Suzatmiko Wijaya (Continuous Education: Journal of Science and Research, 2026)
Conflict is an inseparable part of the dynamics of educational organizations, including madrasahs, because it involves differences in interests, perceptions, task allocation, communication, and patterns of relationships among organizational members. When it is not properly managed, conflict can reduce trust, collaboration, workplace comfort, and organizational effectiveness. This study aimed to analyze the sources and forms of conflict, the resolution strategies applied, and the implications of conflict management for the organizational climate at MA Mutiara Sunggal. A qualitative approach with a single case study design was used. Informants were purposively selected from the head of the madrasah, deputy heads, teachers, and educational staff. Data were collected through semi structured interviews, nonparticipant observation, and document analysis, and were analyzed thematically through coding, categorization, theme development, and interpretation. Data trustworthiness was strengthened through source and method triangulation, informant confirmation, peer discussion, and documentation of the analytical process. The findings indicate that conflict primarily originated from differences in perception, unclear task allocation, delayed information, and imbalanced coordination. Conflict was resolved through open communication, deliberation, mediation by the head of the madrasah, clarification of responsibilities, and follow up on joint decisions. Collaborative and fair strategies contributed to greater trust, communication openness, cooperation, safety, and organizational harmony. The study confirms that conflict management is not merely an action to stop disputes, but also an organizational learning mechanism that can strengthen the madrasah climate and support continuous improvement in educational quality.